Konflik Partai Gerindra dan PKS dalam Proses Pengisian Kekosongan Posisi Wakil Gubernur DKI Jakarta Pengganti Sandiaga Salahuddin Uno Tahun 2018-2020 - Dinda Mutia Khaerun Nisa; Sri Budi Eko Wardani (Jurnal Pemerintahan dan Politik Lokal, 2022)
This journal outlines the conflict that occurred between the Gerindra Party and PKS in the context of the process of filling the vacant position of the Deputy Governor of DKI Jakarta to replace Sandiaga Salahuddin Uno in 2018-2020. Meanwhile, the purpose of writing this journal is to find out the causes of the conflict that occurred between the Gerindra Party and PKS in the process of filling the vacant position of the Deputy Governor of DKI Jakarta. Then in analyzing this, this journal uses qualitative research methods by referring to in-depth interview techniques as primary data sources and studies of a number of relevant documents as secondary data sources. Until finally, the results of the research obtained by this journal indicate that there is a conflict between the Gerindra Party and PKS in the process of filling the vacancy for the position of Deputy Governor of DKI Jakarta to replace Sandiaga Salahuddin Uno caused by differences in views between the two political parties in terms of who has the right to fill the vacant position of deputy governor, the implementation of the fit and proper test mechanism as well as in looking at the causes for the non-processing of the two candidates for deputy governor who had been proposed previously, namely Ahmad Syaikhu and Agung Yulianto.